2022
DOI: 10.3324/haematol.2021.279908
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the use of dynamic analysis of cell-free DNA from aqueous humor and vitreous fluid for the diagnosis and treatment monitoring of vitreoretinal lymphomas

Abstract: The diagnosis of vitreoretinal lymphoma (VRL), a rare subtype of primary central nervous system lymphoma (PCNSL), is challenging. We aimed to investigate the mutational landscape of VRL by sequencing circulating tumor DNA (ctDNA) from aqueous humor (AH) and/or vitreous fluid (VF), as well as the application of ctDNA sequencing to diagnosis and treatment monitoring. Baseline AH and/or VF specimens from 15 VRL patients underwent comprehensive genomic profiling using targeted next-generation sequencing. The molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Several studies demonstrated the presence of MYD88 L265P mutation in the aqueous humor and vitreous fluid of vitreoretinal lymphoma patients. In different PVRL cohorts, the reported sensitivity of MYD88 L265P mutation detection ranged from 25% to 88.9%, with direct Sanger sequencing of polymerase chain reaction (PCR), droplet digital PCR, or sequencing (12)(13)(14)(15)(16)(17)(18)(19). The vitreous fluid samples showed higher positive rate than paired aqueous humor samples (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated the presence of MYD88 L265P mutation in the aqueous humor and vitreous fluid of vitreoretinal lymphoma patients. In different PVRL cohorts, the reported sensitivity of MYD88 L265P mutation detection ranged from 25% to 88.9%, with direct Sanger sequencing of polymerase chain reaction (PCR), droplet digital PCR, or sequencing (12)(13)(14)(15)(16)(17)(18)(19). The vitreous fluid samples showed higher positive rate than paired aqueous humor samples (14).…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, numerous studies have focused on exploring potential ancillary techniques and biomarkers for primary vitreoretinal lymphoma (PVRL) diagnosis. The detection of PVRL characteristic gene mutations, including MYD88 L265P and CD79B , and immunoglobulin gene rearrangement ( 4 , 12 21 ) from aqueous humor or vitreous fluid has been considered effective diagnostic approaches. Meanwhile, elevate aqueous humor or vitreous fluid interleukin-10 (IL-10) levels and elevated IL-10/IL-6 ratios have been considered as useful biomarkers ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the potential role of Nupr1 as a negative regulator of the cell cycle and iron‐induced cell death (ferroptosis), [ 29,31 ] we first examined the cell cycle states of different EHT‐related populations at E10.0/E11.0, including immunophenotypic AECs, HECs and IAHC cells, by Hoechst and Ki67 staining. Notably, no difference in cell cycle status between control and cKO embryos was detected (Figure 2E and Figure S5A, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a recent study revealed that Nupr1, a stress‐responsive molecule involved in multiple biological contexts, is an adult HSC quiescence regulator that coordinates with the p53 signaling pathway. [ 29 ] However, the physiological function of Nupr1 in blood generation during embryogenesis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The 5 most frequently mutated genes found in these patients were proviral integration site for moloney murine leukemia virus-1 (PIM1) in 90.9%; myeloid differentiation primary response protein 88 (MyD88) in 77.3%; CD79B in 50.0%; ETS variant 6 (ETV6) in 50.0%; and interferon regulatory factor 4 (IRF4) in 50.0% (Figure 1G). More PIM1 and IRF4 mutations, but fewer MyD88 mutation were observed in VRL patients than primary central nervous system lymphomas (PCNSL) patients as we previously reported [6]. Although two patients with uveitis were ctDNA-positive, their ctDNA concentrations were low; the observed mutations in the two patients with ctDNA-positive uveitis are uncommon in B-cell lymphomas, and we considered them to be clonal hematopoietic mutations (Supplementary Table S6).…”
mentioning
confidence: 90%